Efektivitas Ekstrak Etanol Daun Pecut Kuda (Stachytarpheta jamaicensis L.) Terhadap Luka Sayat pada Mencit (Mus Musculus) - Sri Rahmawati; Adriyan Suhada; Hardani; Musparlin Halid (Pharmaceutical and Traditional Medicine, 2020)
Horse whip leaf plant (Stachytarpheta jamaincensis) is an herbaceous shrub with a long life span of annual. A cut wound is a wound that occurs because it is cut by a sharp instrument. This study aims to determine the effectiveness of ethanol extract of horse whip leaves on wound healing in mice (Mus musculus) and the most effective concentration to heal cut wounds in mice. This research design uses laboratory experimental methods. With the sample used in each experimental group 5 ekormeencit and the number of groups that will be used is 5 groups so that this study uses 25 tails with 3 treatments, namely treatment (positive control (+), negative control (-), 25%, 50%, 75%). All data were tabulated and analyzed statistically with anova. The conclusion shows that the level of administration of horse whip leaf extract at a concentration of 75% is most effective in healing cut wounds in mice, the healing power of cut wounds when compared to horse whip leaf extract with a concentration of 50% and 25% seen from the average percentage of healing from day 1 to 7.